Is idiosyncratic risk conditionally priced? - Rajnish Mehra; Sunil Wahal; Daruo Xie (Quantitative Economics, 2021)
In Merton (1987), idiosyncratic risk is priced in equilibrium as a consequence of incomplete diversification. We modify his model to allow the degree of diversification to vary with average idiosyncratic volatility. This simple recognition results in a state-dependent idiosyncratic risk premium that is higher when average idiosyncratic volatility is low, and vice versa. The data appear to be consistent a positive state-dependent premium for idiosyncratic risk both in the US and other developed markets.
Keywords: G11; G12; 330; factor models; Idiosyncratic risk; risk premium asset pricing